Relasi Akal dan Kecerdasaan Emosional dalam Menghadapi Pandemi Covid-19 - Tsindi Syifa Fathurrahman; Hasan Mud'is (Program Studi Tasawuf dan Psikoterapi, 2022)
In a pandemic situation that is rife, most people are unable to balance between emotional and mind because there are not a few people who are depressed, stressed, depressed and so on, due to a pandemic which results in a system of working from home, learning from home as well as other social restrictions. Therefore this research aims to provide understanding and knowledge to the public in responding to the pandemic in order to be able to balance between reason and emotional intelligence so as to avoid various mental illnesses and others, and this research uses questionnaire broadcasting through google from, which is The results of questionnaire distribution to 23 people consisting of 26.1% men and 73.9% women can be concluded that of these 23 people can balance the relations of reason and emotional intelligence in several fields.